Study on the Frequency of Endocrine Disorders in Children and Teenagers - Adriana Balan; Marinela Pasareanu; Ana Petcu; Veronica Serban Pintiliciuc (Romanian Society of Oral Rehabilitation, 2012)
Aim The purpose of the study was to evaluate the frequency of endocrine disorders in children and teenagers in Moldova county where the presence of major cranio-maxillo-facial disturbances related to endocrine disorders is a well-known reality. The importance of these results relies in the future management of these diseases both clinical and therapeutic. Materials and Methods In the analytic process of observation and care, we used primarily statistical data from a group of 404 patients (children and teenagers), 157 boys and 247 girls aged between 3.6 and 18.5 years, admitted in the Endocrinology Clinic at St. Spiridon University Hospital, Iasi. Every investigated subject was attributed a recording chart with personal data, name, age, sex, and the residence area. Results and Discussion Specific for the analysed group of patients was the great prevalence of Turner Syndrome, followed by pituitary dwarfism and other growth disorders. Nevertheless there also were patients with Klinefelter Syndrome, gonadal disgenesias or congenital mix oedema. This is why further research in other regional hospitals is needed, in order to elucidate possible zonal characteristics (endemic) of various endocrine disorders. On the other hand, genetic and endocrine syndromes seriously affect the patients' oral health, especially the cranio-maxillo-facial growth in children. Conclusions This high prevalence identified in this region can be explained by a better coordination in the identification and treatment of the children, as a result of a sustained clinical program established by the Endocrinology Clinic, the Human Genetic Centre and other paediatric medicine clinics. The identified disorders imply a careful clinical management performed by both the endocrinologist and the paediatric dentist.